Plebanus and the Village as a Microhistorical Study - Falkowski, Tomasz (Sensus Historiae, 2025)
This paper offers an analytical reading of Krzysztof Zamorski’s monograph, Pleban i wieś [The Plebanus and the Village], within the framework of microhistory - a methodological approach explicitly adopted by the author. Premised on the observation that contemporary interpretations of microhistory frequently suffer from reductionism, the study begins by elucidating the core tenets and ambitions of the field’s progenitors. These encompass: the intensive, “microscopic” scrutiny of specific cases; the identification of local modulations within macro-historical processes; the pursuit of an individual lived experience; the shifting of analytical scales; narrative experimentation; and the utilization of the conjectural paradigm. Having established these criteria, the author posits that Zamorski’s work profoundly aligns with the original ambitions of microhistorians, thereby constituting a rigorous microhistorical study. To substantiate this claim, the second section engages with specific empirical analyses from the monograph, illustrating how Zamorski applies microhistorical concepts and tools to the study of the Tenczynek parish and its inhabitants in the early eighteenth century.